1999
DOI: 10.1177/089686089901900612
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Study of Peritoneal Fluid Kinetics in Infants and Children on Peritoneal Dialysis

Abstract: Objectives To study longitudinal changes in trans-capillary ultrafiltration (TCUF) and marker clearance (MC), as a reflection of lymphatic absorption, in children on peritoneal dialysis (PD). To present data on fluid kinetics in infants younger than 2.5 years, using an intraperitoneal volume of 1200 mL/m2 body surface area (BSA). Design The study involved a 4-hour dwell of 1200 mL/m2 BSA of dialysis fluid containing 3.86% glucose with Dextran 70 as volume marker. Cumulative TCUF and cumulative MC were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…While water is reabsorbed along the Starling forces into the blood capillaries, larger molecules are mainly reabsorbed via lymphatic vessels. Based on dextran uptake, the lymphatic absorption rate has been estimated to be 1.5–2 ml/min/1.73 m 2 in children aged 1–18 years, with 70% higher rates measured in infants younger than two years of age 20 21 . Lower ultrafiltration rates are achieved with icodextrin fluid in infants than in older children, possibly due to higher icodextrin absorption 22 .…”
Section: Discussionmentioning
confidence: 99%
“…While water is reabsorbed along the Starling forces into the blood capillaries, larger molecules are mainly reabsorbed via lymphatic vessels. Based on dextran uptake, the lymphatic absorption rate has been estimated to be 1.5–2 ml/min/1.73 m 2 in children aged 1–18 years, with 70% higher rates measured in infants younger than two years of age 20 21 . Lower ultrafiltration rates are achieved with icodextrin fluid in infants than in older children, possibly due to higher icodextrin absorption 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Our patients, however, were matched for time on PD and analyzed as matched pairs, thereby reducing the difference in chronic changes in the peritoneal membrane between the two groups. Also, previous authors have shown no difference in small solute transport creatinine clearance or TCUF in children on chronic PD up to 33 -55 months (23)(24)(25). As the longest time on PD was 52 months, it is unlikely that any long-term effects on the peritoneal membrane had yet taken place.…”
Section: D/p Ratios For Urea and Creatinine And D T /D 0 Glucose Ratiosmentioning
confidence: 80%